‘Jom Masuk U’ Zone 7 attracted some 40,000 visitors - UMP, PNC
Some 40,000 people comprising students, teachers, parents and residents thronged the Sultan Ahmad Shah International Convention Center (SASICC) in Kuantan for two days on March 16 and 17, 2013 to get the latest information on accreditations, financial aids and entries into institutes of higher learning (IPTs), polytechnics and community colleges.